The Legal Status of Roma in Europe: between National Minority and Transnational People - Memo, Sara (Università degli studi di Trento, 2013)
Recent estimates from the Council of Europe (CoE), rates Romani presence in Europe around 10-12 million individuals. In an imaginary Europe without geo-political borders, these estimates raise Romani population to the 9th most populous community, immediately after Belgians. Notwithstanding their numerical proportion and their historical presence in Europe, both international and national legal instruments designed for minorities are currently unable to comprehensively protect and promote Roma rights. Because of their diffuse and still partially nomadic presence, the existing legal instruments are inappropriate to effectively accommodate Romani needs because they are still ensuing from a Westphalian paradigm which identifies one people in relation with a precise territorial area. Indeed, these legal instruments either apply to social groups traditionally resident in a country (“old” minorities) or to migrants (“new” minorities) but cannot apply to Roma who on the one hand are traditionally living in Europe (as “old” minorities) and on the other hand are still moving from one country to the other (as “new” minorities). This study investigates the possibility of identifying a minimum European set of rights for Roma by means of two complementary conceptual frameworks. The first comparatively identifies best legal practices at the national levels, whereas the second, taking into account the specific distinctive features of Roma compared to other groups, proposes the adaptation of international legal instruments designed for indigenous people to Roma as a ‘European transnational people’. In its comparative part, this study analyzes the legal protection of Roma in terms of, linguistic, social-economic and cultural rights as well as in terms of political representation. The proposal for adapting indigenous peoples’ rights draws from the case of Sami in Northern Scandinavia as the only example of a European indigenous people living transnationally in Europe. The results of this study contribute, both theoretically and ...